Iron accumulation in the ventral tegmental area in Parkinson's disease - Zhang, Dongling; Yao, Junye; Sun, Junyan; Wang, Junling; Chen, Lili; He, Hongjian; Wu, Tao (Frontiers in Aging Neuroscience, 2023)
Introduction The ventral tegmental area (VTA) is less affected compared to substantia nigra pars compacta (SNc) in Parkinson's disease (PD). This study aimed to quantitatively evaluate iron content in the VTA across different stages of PD in order to help explain the selective loss of dopamine neurons in PD. Methods Quantitative susceptibility mapping (QSM) data were obtained from 101 PD patients, 35 idiopathic rapid eye movement sleep behavior disorder (RBD) patients, and 62 healthy controls (HCs). The mean QSM values in the VTA and SNc were calculated and compared among the groups. Results Both RBD and PD patients had increased iron values in the bilateral SNc compared with HCs. RBD and PD patients in the Hoehn–Yahr (H & Y) stage 1 did not show elevated iron values in the VTA, while PD patients with more than 1.5 H & Y staging had increased iron values in bilateral VTA compared to HCs. Discussion This study shows that there is no increased iron accumulation in the VTA during the prodromal and early clinical stages of PD, but iron deposition increases significantly as the disease becomes more severe.